Math

solve the quadratic equation using the square root property.

(2x+5)^2=12

  1. 👍 0
  2. 👎 0
  3. 👁 210
  1. 2x+5 = ±√12
    2x = -5 ±√12
    x = (-5 ± 2√3)/2

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math ~CHECK MY ANSWER~

    1) Which of these is a rational number? a. Pi b. Square root 3 ****** c. Square root 2 d. 1.3 (the # 3 has a line at the top) 2) Which of the following sets contains 3 irrational numbers? a. Square root 120 , n , Square root 3

  2. 7th grade math Ms. Sue please

    2. Shelly sews a blanket that has an area of 170 square feet. It has 30 square blocks, each the same size. What is the approximate length of each side of a block? (1 point) 1 foot 2 feet 3 feet 4 feet 3. Which of these numbers can

  3. algebra

    Which shows the expressions in the order they would appear on a number line from least to greatest? 17 over 9, square root of 6, square root of 15, square root of 30, 3 to the power of 3 3 to the power of 3, square root of 30,

  4. ALGEBRA

    1, Factor each expression x^2 - 10x - 24 A. (x + 4)(x - 6) B. (x + 6)(x - 4) C. (x + 2)(x - 12) D. (x + 12)(x - 2) 2, x^2 - 36 = 0 A. (1 + square root of 3, 1 - square root of 3) B. (-6,6) C. No solution D. None of these 3, Factor

  1. Math

    Lesson 8: Systems of Linear and Quadratic Equations Check my work 1. Solve the system of equations. y = 2x^2 - 3 y = 3x - 1 a. no solution b. (-1/2, 5), (2, -5/2) c. (-1/2, -5/2), (2,5)*** d. (1/2, 5/2), (2, 5) 2.how many real

  2. Pre-Calculus

    Solve 0 = 3x^2 + 5x -1 by completing the square. Express your answer as exact roots. 3(x^2 + 5/3 + 25/36) = -1 (x+ 5/6)^2 = 37/36 sq root( x + 5/6)^2 = sq root (37/36) x + 5/6 = +- sq root 37/6 x = -5/6 +- square root 37 /6

  3. Algebra

    Use the quadratic formula to solve the equation. Give exact answers: 2x^2 -1 = 6x. The choices are: a) -3 + square root(7)/2, -3 - square root(7)/2 b) 3 + square root(11)/2, 3 - square root(11)/2 c) 3 + square root(7)/2, 3 -

  4. Math

    Rationalize the denominator. Assume that all expressions under radicals represent positive numbers. The square root of 3y^4 to the third root divided by the square root of 15x^4 to the third root. Here is what I have so far: I

  1. Algebra

    Solve the quadratic equation by the square root property (2x - 1)2 = 25

  2. Algebra

    Solve the quadratic equation. 3x^2-15x+18=0 I know that the formula to quadratic equation is x=-b+and-(square root)b^2-4ac divided by 2a. I know that a=3, b=-15 and c=18, then subsitute in and get two answers, my problem is that I

  3. maths

    Consider the equation x(square) + 4px + 2q = 0 where p and q are real constants. a) by completing square, show that (x+2p)square =4P(SQUARE)-2q b) Hence show that x= -2p +/- square root(4 p(square) -2p ) c) Use the above results

  4. PRE - CALCULUS

    Solve the quadratic equation by the square root property. (2x + 5)2 = 49 A. {-6, 1} B. {0, 1} C. {-27, 27} D. {1, 6} d?

You can view more similar questions or ask a new question.